HUBUNGAN PERILAKU CERDIK DENGAN KUALITAS HIDUP PENDERITA DIABETES MELITUS (DM) TIPE 2 DIMASA KENORMALAN BARU - Nurasiah, Siti; Saputra, Bayu; Abdur Rasyid , T (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
ABSTRACT Covid-19 is a threatening condition for humans, including people with diabetes mellitus (DM). To prevent the worsening, it is necessary to control the condition of patients with DM using the CERDIK behavior model, which can improve their quality of life. This study aims to determine the relationship between applying the CERDIK behavior model and the quality of life of patients with type 2 DM in the new normal. This is quantitative research with a cross-sectional approach correlation design. The population in this study was 102 people. There were 81 respondents taking part in this study chosen using a non-probability sampling technique. The data were collected using the CERDIK behavior model questionnaire and the WHOQOL-BREEF quality of life questionnaire. This study used univariate and bivariate analysis with the chi-square test. The results showed that, on average, most respondents were age 57; 38.3% had a high school education, 90.1% were female, 61.7% were housewives, and 70.4% had suffered DM for < 5 years. The study also found that there was a relationship between the application of CERDIK model behavior and the quality of life of patients with type 2 DM during the new normal in psychological well-being with a p-value of 0.012 (α <0.05) in social relationships with a p-value of 0.026 (α<0.05), and in the environment with a p-value of 0.034 (α<0.05). In contrast, there was no relationship between applying the CERDIK behavior model and the quality of life of patients with type 2 DM during the new normal in physical health, with a p-value of 0.357 (α<0.05). Public health centers are recommended to promote health and motivate people with DM to continue living healthy life.